Sectorial structure, qualitative characteristics and guidelines of labour mobility in the European Union - Raquel Llorente Heras; Carlos Iglesias Fernández; Juan R. Cuadrado-Roura (European Regional Science Association (ERSA), 2004)
In the context of the process of construction of a single labour market in the Economic Union, one of the greatest problems is the existence of certain levels of structural unemployment. From this point of view, the imbalance between the qualification characteristics of work supply and demand as well as the determining factors of geographical mobility among jobs become a relevant explication factor. The aim of the paper will be to carry out a comparative analysis of some of the most important characteristics of employment in European countries. For this, how different employed population groups are distributed by sectors of activity and labour occupations will be analysed, how these structures have been modified over time, and the patterns of labour mobility that interconnect activities and occupations in the framework of labour mobility, in order to see whether these evolutions are leading to an assimilation of labour characteristics in the countries, or not. Keywords: labour mobility, employment, service sector, European Union. JEL-Code: J62, L80, F02
Keywords: J62; L80; F02; 330; labour mobility; employment; service sector; European Union